2016
DOI: 10.1097/mib.0000000000000662
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Microbiotas are Associated with Ileum-Restricted and Colon-Involving Crohnʼs Disease

Abstract: Ileal and colon-involving CD sustain distinct microbiotas, suggesting that different mechanisms underlie the two major manifestations of CD. The potential contribution of Fusobacterium to inflammation in ileal CD should be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 43 publications
3
37
0
Order By: Relevance
“…Both the twin study by Willing et al 129 and the large study in children126 and adolescents132 did however show differences between the mucosa-associated microbiota in isolated colonic Crohn's disease and UC. 16sRNA pyrosequencing of mucosal samples131 confirms the increase in E. coli and reduced F. prausnitzii in Crohn's disease with ileal involvement with milder changes in isolated colonic disease, although the latter did show some reduction in F. prausnitzii compared with healthy controls. This study also confirmed that the mucosa-associated microbiota is consistent at different sites from ileum to rectum in the same individual.…”
Section: Microbiotamentioning
confidence: 78%
“…Both the twin study by Willing et al 129 and the large study in children126 and adolescents132 did however show differences between the mucosa-associated microbiota in isolated colonic Crohn's disease and UC. 16sRNA pyrosequencing of mucosal samples131 confirms the increase in E. coli and reduced F. prausnitzii in Crohn's disease with ileal involvement with milder changes in isolated colonic disease, although the latter did show some reduction in F. prausnitzii compared with healthy controls. This study also confirmed that the mucosa-associated microbiota is consistent at different sites from ileum to rectum in the same individual.…”
Section: Microbiotamentioning
confidence: 78%
“…Myofibroblasts are activated by a variety of mechanisms including paracrine signals derived from immune and nonimmune cells, autocrine factors secreted by myofibroblasts, pathogen-associated molecular patterns derived from microorganisms that interact with pattern recognition receptors such as Toll-like receptors (TLRs), and the so called damage-associated molecular patterns derived from injured cells, including DNA, RNA, ATP, highmobility group box proteins, microvesicles, and fragments of ECM molecules (1, 14). The intestinal microbiota (15) (1618•) as well as dietary components (1921•) have been recognized to potentially modulate both intestinal inflammation and fibrogenesis. However, at present, neither specific bacterial strains nor specific micronutrients with pro-fibrotic or anti-fibrotic action have been clearly identified.…”
Section: Morphology and Mechanisms Of Intestinal Fibrosismentioning
confidence: 99%
“…However, genetic and microbiome studies have challenged this dogma; for example some studies support a difference between small intestinal-restricted and colonic-involving CD. 1,2 A genetic predisposition to IBD is fundamental and relatives of patients are at enhanced risk of developing IBD themselves. 3,4 The interaction between the gut microbiota and the gut immune system is pivotal in IBD pathogenesis 5 and in patients with IBD abnormalities can be demonstrated in both the gut immune system and the gut microbiota (dysbiosis) as well as alterations in intestinal permeability and increased concentrations of neutrophil-derived calprotectin in faeces.…”
mentioning
confidence: 99%